Therapeutic Communication of Sexual Violence Against Women Victims - Nur Kiblati, Ersa Kireina; Alfi Auliyansah, Muhamad; Putri Nurhalizah, Ratu; Imawan, Khaerudin; Erawati, Dedet (Devotion : Journal of Research and Community Service, 2024)
Sexual violence is one of the acts of direct violence, the act involves other people in the desired sexual activity. Sexual violence that occurs in the community is a particular concern, especially for women. The general public often blames victims who dress openly, this is usually said to be victim blaming or victim blaming, which means that victims of crime are held accountable for what happened to them. The psychological impact experienced by the victims is mostly mental trauma, fear, shame, anxiety, and even suicide attempts. This form of literature research aims to find out the application of therapeutic communication in an effort to recover victims of sexual violence against women and children. In this study, the researcher uses qualitative methods, data collection with interview methods and descriptive observations strengthened by using literature studies with literature searches using therapeutic communication keywords in an effort to recover victims of female sexual violence. Based on the cases faced by providing assistance and counseling to victims, counselors must master the stages in the therapy process, this is aimed at the smooth healing process for victims who experience sexual violence. The stages that must be mastered are; pre-interaction stage; orientation stage; stages of work; and termination stage. Of course, the Friendly People in this case are considered to be quite competent in dealing with victims of sexual violence.